Perspectives on evaluating criminal justice and corrections - Bowen, Erica, 1976-; Brown, Sarah (Bingley, U.K. : Emerald, 2012)
A comprehensive and authoritative overview of issues relating to the evaluation of criminal justice/corrections 'interventions', this unique reference draws on a variety of theoretical, cultural and epistemological perspectives with authors from a range of disciplines and countries. It begins by looking at the purpose of evaluation within criminal justice systems as a historical and conceptual background. Methods outlined for evaluating criminal justice focus on educating readers about the design decisions they may face as evaluators, enabling them to make informed decisions when choosing designs that are not necessarily optimal. It raises the question of who evaluation is for, and a clearly informed discussion of the importance of the full range of stakeholders involved in evaluation and the potential impact of participating in evaluations on different stakeholders is presented. With insight into successful and unsuccessful evaluation from the perspective of those who are being evaluated, and a critical examination of the methodological and conceptual difficulties involved in identifying 'effects', this book concludes by looking ahead to the future of criminal justice evaluation.
Using Theory in Criminal Justice Evaluation / Brad Astbury -- The Risk/Needs/Responsivity Model: The Crucial Features of General Responsivity / L.E. Marshall, W.L. Marshall -- Arguments about Methods in Criminal Justice Evaluation / David Smith -- Treatment of Sexual Offenders: Effective Elements and Appropriate Outcome Evaluations / W.L. Marshall, L.E. Marshall -- Resolving Ethical Issues in Randomised Controlled Trials / Robert F. Boruch, Joe S. Cecil, Herb Turner, Timothy Victor, Jordan M. Hyatt -- Critical Qualitative Theory: Opening up the Black Box of Criminal Justice Interventions / Matt Barnard -- Within-Treatment Change: Finding the Individual in Group Outcomes / Erica Bowen -- Propensity Score Analysis / Sarah Brown -- Developing Offender Engagement: Evaluating Probation Trust Pilots / Sue Rex, Elaine Ellis, Nigel Hosking, Wendy Hyett -- Offenders at the Heart of Evaluation / Barry Kushner, Saville Kushner -- From Text Books to Footpaths: Making Real-World Research Stick at the Coal Face / Ian Lambie, Julia Ioane.
Includes index.
Keywords: Education -- Evaluation; Organization & management of education; Rehabilitation of offenders; Crime & criminology; Corrections -- Evaluation; Criminal justice, Administration of